O13 Sexual behaviour, STI and HIV testing and testing need among men who have sex with men (MSM) pre- and post-COVID-19 restrictions in the UK. (16th June 2022) - Brown, Jack; Reid, David; Howarth, Alison; Mohammed, Hamish; Saunders, John; Pulford, Caisey; Ogaz, Dana; Hughes, Gwenda; Mercer, Catherine
Abstract : Introduction: We examine changes in sexual behaviour, STI & HIV testing and testing need among MSM in the UK pre- and post-COVID-19 restrictions. Methods: An online survey of 1, 309 MSM recruited via social media and Grindr over three weeks in November/December 2021. Questions on sexual behaviour and service use had an approximate three-month lookback period corresponding to a period of no/limited COVID-19 restrictions. Unmet testing need was defined as reporting any new and/or multiple condomless anal sex (CAS) partners without a recent STI/HIV test. MSM recruited through Grindr who were UK-resident, cisgender, aged ≥16 years who reported sex with men in the last year (N=430) were compared to those from a related 2017 survey (N=1914) using multivariable regression to adjust for demographic differences between the samples. Results: Compared to the 2017 survey, sexual risk behaviour was higher in the 2021 survey: ≥1 recent new sex partner (71.5% vs. 81.5%, respectively, aOR=1.80); ≥2 recent CAS partners (30.1% vs. 48.8%, aOR=2.23). Reporting recent testing for STIs/HIV was also higher in late 2021 (37.3% vs. 42.6%, aOR=1.34; and 48.7% vs. 45.1%, aOR=1.27, respectively). However, there was no significant change in the proportion with unmet need for STIs (41.4% vs. 44.2%) and HIV (34.8% vs. 39.3%). Discussion: These large, community surveys of MSM in the UK suggest greater sexual risk behaviour post-restrictions in 2021 compared to 2017. However, while we found no evidence of reduced service accessibility following the removal of most restrictions, there remains considerable unmet STI/HIV testing need among UK MSM.